2022
DOI: 10.9778/cmajo.20210199
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to virtual ambulatory care during the COVID-19 pandemic: a qualitative study of faculty and resident physician perspectives

Abstract: Background: The COVID-19 pandemic resulted in a rapid shift from in-person to virtual care delivery for many medical specialties across Canada. The purpose of this study was to explore the lived experiences of resident physicians and faculty related to teaching, learning and assessment during ambulatory virtual care encounters within the competency-based medical education model. Methods: In this qualitative phenomenological study, we recruited resident physicians (postg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The goal in this study was to improve patient satisfaction with nursing, and the motivation of nursing staff was improved by linking quality of nursing to salary performance after clarifying the goals of nursing management [30]. (3) The CI strategy implements planning and management of the nursing staff's external appearance and internal temperament, making it easier for patients to accept the nursing staff and follow their advice. An increase in nursing satisfaction increases patients' trust in nursing staff and improves their compliance with nursing operations, so patients and their families show increased performance in support of nursing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal in this study was to improve patient satisfaction with nursing, and the motivation of nursing staff was improved by linking quality of nursing to salary performance after clarifying the goals of nursing management [30]. (3) The CI strategy implements planning and management of the nursing staff's external appearance and internal temperament, making it easier for patients to accept the nursing staff and follow their advice. An increase in nursing satisfaction increases patients' trust in nursing staff and improves their compliance with nursing operations, so patients and their families show increased performance in support of nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have shown that in tertiary hospitals, the average daily outpatient infusion room receives more than about 300 patients alone. With the addition of patients' accompanying persons or family members, the average daily population flow in the infusion room is basically at 500-800 visits/day [ 3 ]. At the same time, patients are characterized by limited mobility, organic discomfort, and emotional agitation during infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to patients in the inpatient department, the length of stay (LOS) of patients in the outpatient infusion rooms is generally shorter, and they are more mobile [ 2 ]. The department, however, accommodates a large number of patients and their families, and there are obvious problems such as noisy environment and high crowd density [ 3 ]. The survey shows that in tertiary hospitals, the average daily outpatient infusion room receives more than about 300 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this change led, similar to what has been described in other studies, to a limitation or disappearance of physical examinations, substantially reducing the capacity for learning and teaching. Similarly, the time constraints imposed by virtual modalities translated into fewer teaching moments for residents [57]. This wasworsened by the fact that the patient pro le primarily consisted of respiratory cases infected with COVID-19, as described in the "COVID-19 Monograph" category, which limited their learning opportunities.…”
Section: Discussionmentioning
confidence: 99%